Development, optimization, and evaluation of a nanostructured lipid carrier of sesame oil loaded with miconazole for the treatment of oral candidiasis. (31st December 2022) - Hosny, Khaled M.; Sindi, Amal M.; Ali, Sarah; Alharbi, Waleed S.; Hajjaj, Maher S.; Bukhary, Haitham A.; Badr, Moutaz Y.; Mushtaq, Rayan Y.; Murshid, Samar S. A.; Almehmady, Alshaimaa M.; Bakhaidar, Rana B.; Alfayez, Eman; et al.
Abstract: Candida albicans is the fungus responsible for oral candidiasis, a prevalent disease. The development of antifungal-based delivery systems has always been a major challenge for researchers. This study was designed to develop a nanostructured lipid carrier (NLC) of sesame oil (SO) loaded with miconazole (MZ) that could overcome the solubility problems of MZ and enhance its antifungal activity against oral candidiasis. In the formulation of this study, SO was used as a component of a liquid lipid that showed an improved antifungal effect of MZ. An optimized MZ-loaded NLC of SO (MZ-SO NLC) was used, based on a central composite design-based experimental design; the particle size, dissolution efficiency, and inhibition zone against oral candidiasis were chosen as dependent variables. A software analysis provided an optimized MZ-SO NLC with a particle size of 92 nm, dissolution efficiency of 88%, and inhibition zone of 29 mm. Concurrently, the ex vivo permeation rate of the sheep buccal mucosa was shown to be significantly ( p < .05) higher for MZ-SO NLC (1472 µg/cm 2 ) as compared with a marketed MZ formulation (1215 µg/cm 2 ) and an aqueous MZ suspension (470 µg/cm 2 ). Additionally, an in vivo efficacy study in terms of the ulcer index against C. albicans found a superior result for the optimized MZ-SO NLC (0.5 ± 0.50) in a treated group of animals. Hence, it can be concluded that MZ, through an optimized NLC of SO, can treat candidiasis effectively by inhibiting the growth of C. albicans .